Content of Prussic Acid and Production of Sorghum Brown Midrib by Adding Urea Fertilizer and Extending Harvesting Time - Umami, Nafiatul; Isnaini, Nofi; Suhartanto, Bambang (ANIMAL PRODUCTION, 2019)
Abstract. The aimed of this study to determine the effect of adding urea fertilizer (0, 50, and 100 kg/ha) and harvesting time (50, 80 and days) on prussic acid content and production of the brown midrib (BMR) sorghum plants. This study design was completely randomized factorial 3 x 3. The variables measured were prussic acid content, fresh yield, the production of dry matter (DM) and organic matter (OM). The results showed that content of prussic acid increased and highly significant with the addition of urea. The fresh yield of BMR sorghum is highest in the fertilization of 50 kg/ha and at the harvesting time 80 days. The highest DM production at fertilization 0 kg/ha andÂ  harvesting time 110 day. OM production of the highest is the addition of fertilizer 0 kg/ ha and at the harvesting time on 80 days. From the results of this study concluded that on harvesting time 80 day sorghumÂ  BMR have produces optimum and addition of urea to a level of 100 kg/ha did not affect the content of prussic acid, fresh yield, DM and OM.